Development of STEM Virtual Laboratory in Science Assisted by Articulate Storyline to Empower Self-Regulated Skills and Computational Thinking Skills of Junior High School Students: A Need Analysis - Najah, Safinatun; Indriyanti, Nurma Yunita (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2024)
Science education at the Junior High School level necessitates innovative breakthroughs in developing learning resources that can ignite interest and refine basic skills in students. This research aims to conduct a needs analysis (Need Analysis) as a basis for designing and developing a STEM Virtual Science Laboratory assisted by Articulate Storyline, focusing on empowering Self-Regulated Skills and Computational Thinking Skills in junior high school students. This research method involves surveys, interviews, and tests to identify the specific needs of junior high school students and the challenges they face in learning science. The results of this analysis will guide the design and development of virtual laboratories tailored to student characteristics and needs. The Science Virtual STEM Laboratory was designed utilizing the Articulate Storyline platform, enabling an interactive and immersive learning experience. The primary focus of development is on empowering Self-Regulated Skills, such as self-planning and progress monitoring, as well as developing Computational Thinking Skills, including problem-solving and algorithmic thinking. The results of this research can serve as a foundation for developing innovative and relevant learning tailored to students needs in the digital era. Additionally, implementing the STEM Virtual Science Laboratory can mark the initial stride in preparing students to tackle the increasingly complex and technology-based challenges of future learning and work.